ASSESSMENT OF WATER LOSSES FROM BADOVC LAKE, KOSOVO: ISOTOPIC IMPLICATIONS - Skender, B.; Arjan, B. (Bulletin of the Geological Society of Greece, 2016)
This paper aims to quantitatively assess water losses of Badovc Lake - Kosovo based on both water balance of the lake and water isotopic composition of H-2 and O-18. According to lake water balance, a water loss of 3,738,905 m³ for the hydrologic year 2014, was evaluated. These consistent data favour the opinion that a continuous groundwater outflow from the lake is present and it is conditioned by the intensively developed fracture system in the lake basement formations. This was also supported by the isotopic analysis (H-2 and O-18) of the sampled waters. Most of water samples taken from hydrologic components of Lake Badovc fall on a linear plot of δ2H versus δ18O showing an isotopic variation typical for waters evaporated from a lake and fits very well with Global Meteoric Water Line (GMWL), while two rain water samples are isotopically lighter (more negative δ values). Water samples taken from water leakages on the right side of the dam, the piezometer, two wells drilled in the valley downstream of dam, Hajvalia mine gallery and the water flow downstream of the dam, have isotopic composition similar with that of the lake water. Water of Hajvalia mine well shows isotopic composition that falls between that of rain water and lake water. Considering δ values of rain water (δ2H= -129.6‰, δ18O= -16.56‰) and lake water (δ2H= -67.2‰, δ18O= -9.20‰) and mine water (mixture) (δ2H= -73.3‰, δ18O= -10.15‰) was found that the fraction of rain water in mine water ranges from 6% (according H-2) to 10% (according O-18), while the fraction of lake water in mine water varies from 94% (according H-2) to 90% (according O-18).